Broadcast news [videorecording (DVD)] - Brooks, James L.; Brooks, James L.; Brooks, James L.; Hurt, William; Brooks, Albert, 1947-; Hunter, Holly, 1958- (Criterion collection, 2010)
A caustic inside look at the Washington news media, stars Holly Hunter in her breakout role, as a feisty television producer torn between an ambitious yet dim anchorman and her closest confidant, a cynical veteran reporter. James L. Brooks' witty, gently prophetic entertainment is a captivating transmission from an era in which ideas on love and media were rapidly changing.